Circuit theory extended: The role of speculation in crises - Neil Lancastle (Kiel Institute for the World Economy (IfW), 2012)
This paper asks why modern finance theory and the efficient market hypothesis have failed to explain long-term carry trades; persistent asset bubbles or zero lower bounds; and financial crises. It extends Keen (Solving the Paradox of Monetary Profits, 2010) and the Theory of the Monetary Circuit to give a mathematical representation of Minsky's Financial Instability Hypothesis. In the extended model, the central bank rate is not neutral and the path is non-ergodic. The extended circuit has survival constraints that include a living wage, a zero interest rate and an upper interest rate. Inflation is everywhere. The possibility of a high interest rate, hedge economy emerges, where powerful banks invest surplus loan interest. With speculation, banks lobby to enter investment markets and the system is precariously liquid/illiquid. The paradox of a Ponzi economy, where loans never get repaid, is that private banks must speculate to increase reserves and rely on systemic crises to rebuild their balance sheets. Estimating model parameters for the US gives a scissor-graph like the The Financial Crisis Inquiry Commission (The Financial Crisis Inquiry Report, 2011) with other nuances, namely i) a heart attack in 1973-1974 that corresponds to the collapse of Bretton Woods ii) an accelerated decoupling of household wages and loans after the repeal of Glass-Steagall. Simulating bank bailouts, household bailouts and a Keynesian boost suggests that bank bailouts are the least effective intervention, with downward pressure on wages and household spending. Bailing out hedge households is a form of monetary contraction, and boosting hedge business loans is a form of monetary expansion. The appropriate policy choice would seem to depend on the external balance and inflation concerns. The paper concludes that, with international Ponzi sectors, viable resolution mechanisms include reparations (dL < 0), turning Ponzi debt into equity or junk debt (dL → ∞), household bailouts and a Keynesian boost.
Keywords: E10; E27; E43; E58; E60; 330; circuit theory; macroeconomic simulation; carry trade; banking regulation; interest rate policy; Finanzmarktkrise; Wirtschaftliche Instabilität; Geldtheorie; Geldumlauf; Wertpapierspekulation; Bankenpolitik; Zinspolitik; Theorie